Literary Translations in the Book Production of Estonian Exile Publishers - Möldre, Aile (chronotopos – A Journal of Translation History, 2024)
The article treats the activities of Estonian exile publishers in the Soviet Union (1918–1937) and in the West (1944–1991), concentrating on the publications of translated literary works. The analysis includes the study of the motives for publishing literary translations and the functions these publications were supposed to fulfil in these two different contexts of production and reception. The publishing of Estonian-language literary works in the Soviet Union is studied in the framework of national and cultural policies of the 1920s and 1930s, which determined the development of minority publishing. The output of translated literature by Estonian-language publishers is compared with the all-union translation policy and its preferences in the selection of authors for translation. The treatment of the Estonian-language publishing in the West focuses on the activities of Andres Laur and his publishing house Orto that issued most of the literary translations. The translation publications by other publishers (Vaba Eesti, Eesti Kirjanike Kooperatiiv) represent alternative modes of selection, illustrating the variety of motives.